Local and regional climatic controls on high-resolution rainfall and cave dripwater oxygen isotopes in northern Borneo - JW, Moerman; KM, Cobb; JF, Adkins; H, Sodemann; B, Clark; AA, Tuen (American Geophysical Union, 2012)
The relationship between climate variability and rainfall isotopic variability is poorly constrained, especially in the tropics, where many key high-resolution paleoclimate records rely on past rainfall isotopes as proxies for hydroclimate. Multi-year, high-resolution monitoring studies of modern rainfall isotopes are needed in order to inform interpretations of isotope-based paleoclimate reconstructions, yet such studies are rarely undertaken. Here we present a daily-resolved, 5-yr-long timeseries of rainfall oxygen isotopes (delta18O) and 3-yr-long timeseries of bi-weekly dripwater delta18O from Gunung Mulu National Park, located in northern Borneo (4° N, 114° E), which we compare to instrumental records of local precipitation amount as well as globally-gridded climate variables. Daily variations in rainfall delta18O, ranging from +0.5 to -18.50/00, exhibit an inverse relationship with daily local precipitation amount (R = -0.20, p < 0.05), evidence of the 'amount effect'. We observe a stronger amount effect relationship when we compare daily rainfall delta18O values to the average of local precipitation amount over the preceding week (R = -0.46, p < 0.01). Similarly strong correlations for monthly averaged Mulu rainfall delta18O and precipitation amount (R = -0.57, p < 0.01) highlight the time-integrative nature of rainfall delta18O. A relatively weak bi-model seasonal cycle in rainfall delta18O of 2-30/00 is overshadowed by large, negative delta18O anomalies of up to 160/00 that persist for several days every 30-90 days, closely associated with the Madden-Julian Oscillation. Interannual rainfall delta18O anomalies of 6-80/00 are highly correlated with indices of the El Niño Southern Oscillation (ENSO), such that relatively dry El Nino conditions are associated with higher rainfall delta18O values, and vice versa during La Nina events. Mulu rainfall delta18O is highly correlated to basin-scale interannual climate variability, highlighting the advantages of using water isotope-based proxies, such as stalagmite delta18O, for hydroclimate reconstruction. Mulu cave dripwater delta18O samples taken from three distinct sites during the study period of the rainfall delta18O timeseries strongly reflect the interannual signal of amount-weighted Mulu rainfall delta18O (R = 0.90; 0.88; & 0.64). The dripwater timeseries most closely tracks a 2-3-month average of the rainfall delta18O timeseries, with a 1-2 month lag evident in the dripwaters. There is no difference in the absolute value of rainfall delta18O and dripwater delta18O over the study period, suggesting that evaporation is not an important source of dripwater delta18O variability in the Mulu karst system. We conclude that the three Mulu drips studied here are characterized by residence times of 2-3 months, over which time appreciable mixing occurs in the epikarst. While the 60/00 interannual variations of Mulu rainfall delta18O are largely preserved in both the fast [35 drips per minute (dpm)] and slow (7 dpm) dripping sites in Wind Cave, signal amplitude is reduced to approximately 30/00 at the moderate (14 dpm) dripping site in Lang's Cave. Overall, our study illustrates the great potential to reconstruct past ENSO variability from sufficiently fast-growing northern Borneo stalagmites, and more generally, strongly supports the interpretation of northern Borneo stalagmite delta18O records as proxies for regional hydroclimate variability.